ATIVIDADE ANTIMICROBIANA DE ACTINOBACTÉRIAS DE SOLOS DE COMPOSTAGEM DE ÓLEO DE PALMA (ELAEIS GUINEENSES) CONTRA BACTÉRIAS PATOGÊNICAS DE IMPORTÂNCIA CLÍNICA - Uesugi, Juliana; Ferreira Fernandes, Caroline; Dos Santos Caldas, Daniel; Farias Coelho, Brunna Beatrys; Veloso Bezerra, Nilson (Interfaces Científicas - Saúde e Ambiente, 2024)
Actinobacteria are Gram-positive bacteria known for forming filamentous structures named mycelium and hyphae. They stand out from other bacteria by their high production of secondary metabolites with antimicrobial properties. Composting sites are favorable to produce these metabolites due to the competition patterns held by the presence of a large number of microorganisms. The importance of actinobacteria turns out in the multidrug-resistant bacteria scenario, a consequence of selective pressure on pathogenic bacteria, directly related to the wrong antibiotic administration. This research aimed to evaluate the antimicrobial potential of actinobacteria isolated from composting soil against five clinical importance pathogenic bacteria. The experiment used the direct sensibility test method, and the antimicrobial potential was verified by the presence of an inhibition halo around the bacterial colonies. Between the isolates, seven strains showed inhibitory effects on the growth of at least one of the pathogenic bacteria tested. The results of this research demonstrated that actinobacteria can be an important source of antimicrobial biomolecules which can be used to develop new drugs.